Reliability and Security in the Implementation of Digital Health Service Application with the Application of "Reliability Certification or Electronic Certification" based on Indonesian Law - Charles Amirul Hanif; Muhamad Amirulloh; Helitha Novianty Muchtar (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2021)
Societies are always changing rapidly. Initially, societies recognize ordinary health services. Now, people acknowledge web application based digital health services. This rapid change raises potential problems such as the sale of illegal drugs, user data theft, and illegal health workers. Unfortunately, the government has not provided actions to respond the issues quickly. There is no law that underlies the implementation of web application. It increases the possibility of other potential problems. Therefore, it is necessary to question the reliability and security of the implementation of the application and the form of legal responsibility of the organizer. This study used a normative juridical method, which is carried out by examining secondary data as the main study material. The study reveals that the reliability and security in the implementation of applications both as an electronic system and as a health service facility can still be optimized. There are two forms of legal responsibility for the application operator, namely liability in the form of obligations and in the form of sanctions. DOI: https://doi.org/10.22304/pjih.v8n3.a6